Using molecular markers to investigate genetic diversity, mating system and gene flow of Neotropical trees - Vinson, C; Mangaravite, E; Sebbenn, A; Lander, T (Springer, 2018)
Genetic analysis provides a robust method for understanding the ways in which human interventions in ecosystems may affect genetic diversity and species survival, providing an empirical basis for evidence-based conservation and management planning. This review aims to (1) describe the most informative and widely used molecular markers for genotype analysis, and describe the methods for using that genotype data to understand (2) genetic diversity and structure; and (3) mating system, pollen and seed dispersal. For each area of investigation, we discuss the types of analyses that can be performed, the software available for the analyses, what the analyses indicate, and provide examples from the literature of studies using these approaches. The review focuses on Neotropical tree species because Neotropical forests are highly diverse and are under particular threat from anthropogenic land-use change, and trees are useful model organisms to investigate patterns over evolutionary time and across geographical space.